The Influence Of Product Quality And Price On Product Purchase Decisions - Haryantini, Haryantini; Watiningsih, Ferdina (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2023)
This research aims to determine the influence of price and product quality on purchasing decisions at the distributor PT Saridewi Natural Kosmetik. The design of this research is quantitative descriptive analysis. The population in this study were all consumers who had tried Dewi Skin Care products and the research sample consisted of 99 respondents.The sampling technique used is Probability Sampling with Random Sampling type. Data analysis methods use data instrument tests, classical assumption tests, simple linear regression tests & multiple linear regression, correlation tests, determination tests, hypothesis tests.The research results show that Price (X1), Product Quality (X2), simultaneously have a significant effect on Purchasing Decisions (Y) seen from the hypothesis test.Thus, Ho is rejected and Ha is accepted. Therefore, there is a simultaneous influence between price and product quality on purchasing decisions